Supercharge End-to-Side Sensory Transfer to A Long Nerve Graft to Enhance Motor Regeneration in A Brachial Plexus Model—An Experimental Rat Study - Daniel, Bassem W.; Giesen, Teun; Lu, Johnny Chuieng-Yi; Chang, Tommy Nai-Jen; Zavala, Abraham; Chuang, David Chwei-Chin (Journal of Reconstructive Microsurgery, 2022)
Background Long nerve grafts will affect muscle recovery. Aim of this study is to investigate if supercharged end-to-side (SETS) sensory nerve transfer to long nerve graft can enhance functional outcomes in brachial plexus animal model.Methods A reversed long nerve graft (20–23-mm) was interposed between C6 and musculocutaneous nerve (MCN) in 48 SD rats. The sensory nerves adjacent to the proximal and distal coaptation sites of the nerve graft were used for SETS. There were four groups with 12 rats in each: (A) nerve graft alone, (B) proximal SETS sensory transfer, (C) distal SETS sensory transfer, and (D) combined proximal and distal SETS sensory transfers. Grooming test at 4, 8, 12 and 16 weeks, and compound muscle action potentials (CMAP), biceps tetanic muscle contraction force, muscle weight and MCN axon histomorphologic analysis at 16 weeks were assessed.Results Grooming test was significantly better in group C and D at 8 weeks (p = 0.02 and p = 0.04) and still superior at 16 weeks. There was no significant difference in CMAP, tetanic muscle contraction force, or muscle weight. The axon counts showed all experimental arms were significantly higher than the unoperated arms. Although the axon count was lowest in group C and highest in group D (p = 0.02), the nerve morphology tended to be better in group C overall.Conclusion Distal sensory SETS transfer to a long nerve graft showed benefits of functional muscle recovery and better target nerve morphology. Proximal sensory inputs do not benefit the outcomes at all.
Keywords: SETS; sensory nerve transfer; long nerve graft; muscle function outcomes; brachial